Smart-watch-programmed green-light-operated percutaneous control of therapeutic transgenes - Maysam Mansouri; Marie-Didiée Hussherr; Tobias Strittmatter; Peter Buchmann; Shuai Xue; Gieri Camenisch; Martin Fussenegger (Nature Communications, 2021)
Wearable smart devices often have green light diodes to monitor health. Here the authors use this to control a light-activated genetic switch for GLP1 production in diabetic mice.